2020
DOI: 10.3390/nu12010235
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery in Obesity: Effects on Gut Microbiota and Micronutrient Status

Abstract: Obesity is associated with reduced gut microbial diversity and a high rate of micronutrient deficiency. Bariatric surgery, the therapy of choice for severe obesity, produces sustained weight loss and improvements in obesity-related comorbidities. Also, it significantly alters the gut microbiota (GM) composition and function, which might have an important impact on the micronutrient status as GM is able to synthesize certain vitamins, such as riboflavin, folate, B12, or vitamin K2. However, recent data have rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
121
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(130 citation statements)
references
References 191 publications
0
121
1
8
Order By: Relevance
“…Success of bariatric surgery implies the recovery of gastric microbial diversity [88] and is associated with the recovery of NO production [46,89]. Over use of antibiotic therapy has been associated with obesity [90].…”
Section: Overweight or Obesitymentioning
confidence: 99%
“…Success of bariatric surgery implies the recovery of gastric microbial diversity [88] and is associated with the recovery of NO production [46,89]. Over use of antibiotic therapy has been associated with obesity [90].…”
Section: Overweight or Obesitymentioning
confidence: 99%
“…For this reason, small bowel EBMT may be promising also in the setting of NAFLD in which the metabolic alterations are similar to those that occur in DM2 36 . Whether the effects of intestinal EBMT may be partly related to changes in gut microbiota, as it is observed in Roux‐en‐Y bypass, 37 it is still unknown.…”
Section: Duodenal Devicesmentioning
confidence: 99%
“…Several studies have evaluated the relation between gut microbiota changes and the improvement in anthropometric and metabolic variables after bariatric surgery. Animal and human studies have reported common changes after bariatric surgery such as a decrease in the abundance of Firmicutes and an increase in Bacteroidetes, Proteobacteria and its class Gammaproteobacteria (order Enterobacteriales , family Enterobacteriaceae , genus Escherichia ) [ 12 ]. Also, gut microbiota is affected by bariatric surgery in a procedure manner, higher levels of Akkermansia , Eubacterium , Hemophilus and Blautia have been shown in sleeve gastrectomy, whilst in Roux-en-Y gastric bypass Veillonella , Slackia , Granucatiella and Acidaminococcus occurred with greater levels [ 13 ].…”
Section: Introductionmentioning
confidence: 99%